Primary and Booster Mucosal Immune Responses to Meningococcal Group A and C Conjugate and Polysaccharide Vaccines Administered to University Students in the United Kingdom - Zhang, Q. (American Society for Microbiology, 2001)
Meningococcal group A+C capsular polysaccharide (PS) conjugate vaccines may prime for serum immunoglobulin G (IgG) memory responses to meningococcal capsular PS. It is not known whether these vaccines induce immunological memory at the mucosal level, which may be important in reducing nasopharyngeal carriage. Mucosal immune responses to meningococcal conjugate and PS vaccines in young adults were investigated. Healthy university students were randomized to receive either a groups A+C meningococcal conjugate vaccine (MACconj, n = 100) or a group A+C meningococcal PS vaccine (MACPS, n = 95). One year after the primary immunization, both groups were randomized again to receive a MACconj or a MACPS booster vaccination. Saliva samples were collected before and 1 month after the primary and booster vaccinations. Anti-meningococcal A (MenA) and C (MenC) PS IgA and IgG antibody levels were measured by a standard enzyme-linked immunosorbent assay. After the primary vaccination, salivary MenA and MenC IgG and MenA IgA concentrations were significantly increased after immunization with both MACconj and MACPS vaccines, but the salivary Men C IgA level was increased only after MACPS vaccine (P < 0.01). IgA responses to both serogroups were greater for MACPS than MACconj vaccine (P < 0.05), whereas no significant differences were seen for IgG responses. MenA IgG titers were higher after the MACPS booster in MACconj-primed subjects than after the MACPS primary vaccination, suggesting the presence of IgG memory. Antibody responses to a dose of either MACPS or MACconj were not significantly reduced in those previously given MACPS compared to the primary responses to those vaccines. Meningococcal A+C conjugate and PS vaccines induce significant mucosal responses in young adults. MACconj priming may induce IgG memory at the mucosal level, which is likely to be a reflection of an anamnestic serum IgG response. No evidence of mucosal hyporesponsiveness was observed after MACPS priming in this study.